Dark Mountain - Carson, Jef (United States Cross Atlantic Publishing, 2017)
When a dead body is discovered stuffed inside a car trunk in the forest outside Rocky Points, Colorado, Chief Detective David Wolf finds himself involved in a case that will rock the local community. But as details emerge, the tension rises higher when it's clear the driver's last client was Tom Rachette, Wolf's loyal detective. Worse yet, Detective Rachette is no longer answering his phone. At the same time, Wolf gets a cryptic email that jars loose war memories he'd rather forget. And it soon becomes clear he must face his past head-on if he wants to save his friend from certain death. Meanwhile, Heather Patterson, Wolf's former detective who has since moved on from her days in the Sluice-Byron County SD, receives a cryptic message herself. She's left the department to forget brutal events that now have her cracking at the seams. But ready or not, she has no choice but to step back into the fire. Because the messages contain a lot of blood and demand two things: Find David Wolf and come now. Or he dies.
106577
Keywords: Murder -- Investigation -- Fiction; Sheriffs -- Fiction; Colorado -- Fiction; Detective and mystery fiction; Fiction; Mystery fiction